If sec theta+tan theta=m,sec theta-tan theta=n,find √mn
Answers
Answered by
159
Hi ,
Here I am using A instead of they ,
SecA + tanA = m ----( 1 )
SecA - tanA = n -----( 2 )
Multiply ( 1 ) and ( 2 ) , we get
Sec² A - tan² A = mn
1 = mn
mn = 1
√mn = √1
√mn = 1
I hope this helps you.
:)
Here I am using A instead of they ,
SecA + tanA = m ----( 1 )
SecA - tanA = n -----( 2 )
Multiply ( 1 ) and ( 2 ) , we get
Sec² A - tan² A = mn
1 = mn
mn = 1
√mn = √1
√mn = 1
I hope this helps you.
:)
Answered by
51
hope it may help.....
Attachments:
![](https://hi-static.z-dn.net/files/d59/add540a3404159b374459700e761911e.jpg)
Similar questions